Analisis Kesadaran Keberlanjutan Peserta Didik terhadap Lingkungan - Zulkarnaen Zulkarnaen; Riandi Riandi; Amprasto Amprasto (Postgraduate, University of Mataram, 2023)
This study aims to analyze the sustainability awareness of students at SMAN 1 Ciasem, Subang, West Java which is adjusted to environmental pollution material. The method used in this research is descriptive method with a quantitative approach. This research was conducted at SMAN 1 Ciasem with a total sample of 30 students. The instrument used in this study was a questionnaire consisting of 20 statements consisting of 10 positive statements and 10 negative statements. The results in this study include the average value and percentage of students' awareness of sustainability in general, based on indicators, and gender. The mean value for positive statements of students' awareness of sustainability is 3.14 and for negative statements, it is 1.89 in the high category. In addition, this study also produced data in the form of differences in sustainability awareness based on gender. The average percentage of male students' sustainability awareness in positive statements was 77.19% and that of women was 78.86%. The conclusion in this study is that students' awareness of sustainability has a high category. This indicates that students carry out habits that always pay attention to sustainability awareness. Based on their gender, female are more aware of sustainable environmental sustainability than male